Cetobacterium somerae-derived argininosuccinic acid promotes intestinal and liver ureagenesis to alleviate ammonia intoxication - Shidong Wang; Xue Li; Muzi Zhang; Ming Li (Microbiome)
Abstract Background Ammonia generated from amino acid metabolism is a cytotoxin that can adversely affect cell function and overall health and potentially lead to cellular toxicity and death due to its accumulation. Previous studies have shown that acute ammonia intoxication (AI) can increase the intestinal C. somerae abundance, hinting at a possible involvement of C. somerae in the host's reaction to AI. Nonetheless, the precise mechanism through which C. somerae mitigates the effects of AI is uncertain. Results This research elucidated the metabolic mechanism of transplanting Cetobacterium somerae ceto (CSC) to assist the host in managing AI. Our results suggest that (I) AI resulted in impaired ureagenesis pathway. This was manifested by elevated levels of ammonia in the blood, liver, and intestines, along with decreased urea levels. (II) Supplementing orally with live CSC facilitated its colonization in the intestines, mitigating AI by reversing depletion of intestinal argininosuccinic acid (ARA) and promoting ureagenesis. (III) CSC synthesized ARA from aspartate and asparagine through the asnA-ansA/B-argG gene cluster. Additionally, CSC assimilated fumaric acid and malic acid from the environment, dampening the degradation of ARA by CSC’s fumA-fumB-argH gene cluster. (IV) Live CSC provided ARA support for ureagenesis in the intestine and liver, reducing endogenous ammonia levels of pseudo-sterile yellow catfish. (V) Supplementation of ARA decreased systemic ammonia levels by promoting ureagenesis. Inhibiting the expression of argininosuccinate lyase in the liver through RNA interference can impede arginine synthesis, thereby eliminating the ammonia-lowering effect of ARA. Conclusion In summary, this study found that the role of probiotics in enhancing the host's resistance to AI depends on the function of ARA generated by CSC. AI can lead to depletion of ARA and interrupting ureagenesis, while CSC-produced ARA supplements ureagenesis in the liver and intestines, facilitating ammonia detoxification into urea. Video Abstract